Overexpression of HSFA4A and RAP2.12 transcription factors in Arabidopsis thaliana confers tolerance to various abiotic stresses - ANDRÁSI, Norbert; RIGÓ, Gábor; ZSIGMOND, Laura; SZABADOS, László (Studia Universitatis Babeș-Bolyai Biologia, 2025)
Transcription factors are part of stress-signaling pathways, controlling activation of stress-responsive target genes. Heat shock factors and ethylene response factors can regulate responses to extreme temperature, salinity, drought, heavy metals, oxidative damage and anoxia. Arabidopsis HEAT SHOCK FACTOR A4A (HSFA4A) is part of the mitogen-activated protein kinase signaling pathway and was previously shown to regulate responses to salt, oxidative and heat stresses as well as their combinations. The RELATED TO APETALA2.12 (RAP2.12) factor was shown to be involved in anoxia, oxidative and osmotic stresses, and to modulate sensitivity to abscisic acid (ABA). Here we show that overexpression of HSFA4A and RAP2.12 can increase the survival rate of Arabidopsis plants exposed to heat, salt or osmotic stresses and combinations of high temperature with salt or osmotic stresses. Moreover, overexpression of these factors improved photosynthetic activity in such adverse conditions. Photosynthetic performance of the hsfa4a and rap2.12-2 mutants was variable in plantlets stressed in sterile conditions and less affected in soil-grown mutants when exposed to drought stress. Our data clearly indicate that these factors are implicated in stress response control, although their precise function remains to be elucidated. Article history: Received 18 February 2025; Revised 11 November 2025; Accepted 15 November 2025; Available online 20 December 2025